2014
DOI: 10.1371/journal.pone.0095476
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Antibiotics on Human Gut Microbiota

Abstract: From birth onwards, the human gut microbiota rapidly increases in diversity and reaches an adult-like stage at three years of age. After this age, the composition may fluctuate in response to external factors such as antibiotics. Previous studies have shown that resilience is not complete months after cessation of the antibiotic intake. However, little is known about the short-term effects of antibiotic intake on the gut microbial community. Here we examined the load and composition of the fecal microbiota imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
213
5
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(253 citation statements)
references
References 35 publications
21
213
5
9
Order By: Relevance
“…The result is in line with previous studies showing that antibiotics reduce microbiota stability and diversity (Rehman et al, 2012;Panda et al, 2014). We found that the abundance of Clostridium cluster XIVa was significantly decreased in the next sample after antibiotic course.…”
Section: Discussionsupporting
confidence: 93%
“…The result is in line with previous studies showing that antibiotics reduce microbiota stability and diversity (Rehman et al, 2012;Panda et al, 2014). We found that the abundance of Clostridium cluster XIVa was significantly decreased in the next sample after antibiotic course.…”
Section: Discussionsupporting
confidence: 93%
“…Bacteroides develops natural resistance to antibiotics, and particularly to penicillin antibiotics, by producing β-lactamase, and several reports have shown that the ratios of Bacteroides are increased in the presence of β-lactams, such as ampicillin. [25][26][27] Our present finding that Bacteroides were increased by continuous ampicillin treatment tended to be similar to these previous reports. From the results on purgative action, which continued throughout the eight days of ampicillin treatment, the purgative action of SA was inhibited, but that of DKT was increased, which proved that RG was involved in these effects.…”
Section: Discussionsupporting
confidence: 92%
“…Recent evidence from humans indicates that the use of the most common antibiotics, β-lactams and macrolides, not only disturbs the composition of the gut microbiota (by decreasing its diversity and reducing the number of core taxa (97), but can also affect many metabolic functions, including sugar metabolism and synthesis and degradation of intestinal/colonic epithelium components (98). Resilience of the gut microbiota often takes months after the cessation of the antibiotic use, although there are great variations between different antibiotics; their effect on the gut microbiota is dependent on the properties of the antimicrobial agent, and the structure, function and resistance genes of the microbial community (99).…”
Section: Antibioticsmentioning
confidence: 99%